Spine Trauma Classifications: Historical, Current, and Emerging Perspectives for Radiologists - Nandolia, Khanak; Saran, Sonal; Varshney, Garima; Shirodkar, Kapil; Iyengar, Karthikeyan P.; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2025)
The spine serves as a protective, load-bearing, and stabilizing axis for the body. Trauma can cause significant damage to spinal structures, potentially resulting in severe neurological dysfunction and disabilities such as paraplegia or quadriplegia. Early and accurate diagnosis of these injuries is important, with computed tomography and magnetic resonance imaging being important for recognizing these injuries and guiding timely treatment to minimize disability. Radiologists play a critical role in assessing spine trauma to determine stability, which informs the need for nonoperative or operative management. Trauma classification systems are vital for uniform communication between radiologists and surgeons, aiding in decision-making. Various classifications exist for cervical, thoracolumbar, and sacral trauma, each with advantages and limitations. Understanding these classification systems is essential for guiding diagnosis, treatment, and prognostication. Over the years, these systems have evolved, reflecting advancements in medical knowledge, imaging technology, and clinical practices. Contemporary classification systems have addressed the limitations of previous systems. Vaccaro et al proposed the “Thoracolumbar Injury Classification and Severity Score (TLICS)” in 2005 and the “Subaxial Cervical Spine Injury Classification System” in 2007. These classifications focus on injury morphology, the integrity of the posterior ligamentous complex or discoligamentous complex, and the patient's neurologic status. The Arbeitsgemeinschaft für Osteosynthesefragen (AO) founded the “Spine Classification Group” to review the “AO-Magerl classification” and create an extensive system for the whole spine. This system focuses on fracture morphology, neurological status, clinical modifiers, and facet joint injury. The TLICS system is straightforward and easy to use in clinical practice, while the AOSpine system is more comprehensive and reliable. As classification systems evolve, collaboration among radiologists, spine surgeons, and researchers will be essential. By embracing advancements in imaging technology and incorporating new clinical data, the field of spine trauma classification can achieve greater accuracy and consistency, ultimately enhancing patient care and outcomes.
Keywords: spine trauma; TLICS; AO; CT; MRI